1990
DOI: 10.1210/jcem-70-4-1167
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Glucose Metabolism in Human Hyperthyroidism

Abstract: The present study was designed to determine the effect of spontaneous hyperthyroidism on the forearm muscle glucose uptake and oxidation during the postabsorptive state and after an oral glucose challenge. Ten normal subjects and 11 hyperthyroid patients were studied after an overnight fast (12-14 h) and for 3 h after ingestion of 75 g glucose. Peripheral glucose metabolism was analyzed by the forearm technique to estimate muscle exchange of substrate combined with indirect calorimetry. Increased forearm gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
3
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 35 publications
8
41
3
3
Order By: Relevance
“…Hypersomatotropism is associated with disturbance of glucose tolerance and insulin resistance. Hyperprolactinaemia, like hypersomatotropism, is associated with decreased insulin sensitivity (Foss et al, 1995). The present study (on control group) demonstrated that prolactin increases progressively from the first trimester through till third trimester.…”
Section: Discussionsupporting
confidence: 56%
“…Hypersomatotropism is associated with disturbance of glucose tolerance and insulin resistance. Hyperprolactinaemia, like hypersomatotropism, is associated with decreased insulin sensitivity (Foss et al, 1995). The present study (on control group) demonstrated that prolactin increases progressively from the first trimester through till third trimester.…”
Section: Discussionsupporting
confidence: 56%
“…Although GH has been established to have a primary role in this phenomenon (Davidson 1987), several studies indicate that PRL is also capable of antagonizing insulin action (Landgraf et al 1977, Schernthaner et al 1985, Foss et al 1995, Reis et al 1997. Increased responsiveness of plasma glucose to insulin in Ames dwarf mice, which are deficient in these hormones, is consistent with the diabetogenic effect of GH and PRL (Borg et al 1995).…”
Section: Discussionmentioning
confidence: 97%
“…In humans and animals, glucose intolerance, insulin resistance and hyperinsulinemia are associated with excess of GH (Rizza et al 1982, Ader et al 1987, Davidson 1987 or PRL (Landgraf et al 1977, Schernthaner et al 1985, Foss et al 1995, Reis et al 1997, while deficiency of these hormones leads to increased insulin sensitivity, decreased insulin secretion and hypoglycemia (Hopwood et al 1975, Bougneres et al 1985, Daugaard et al 1999. GH and PRL have been shown to promote tyrosine phosphorylation of IRS-1 and IRS-2 and their association with PI 3-kinase both in vitro (Souza et al 1994, Argetsinger et al 1995, Ridderstråle et al 1995, Berlanga et al 1997 and in vivo (Yamauchi et al 1998, Thirone et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Our results agree with previous studies, on patients treated with atypical antipsychotics drugs like haloperidol and showed that they are more likely to develop diabetes and hyperglycemia (22) . Hyperglycemia could be related to the hyperprolactinemia caused by the typical antipsychotics drugs as causing an increased insulin resistance (23) . Haloperidol antagonizes dopamine D2 receptors, and the activation of these receptors enhances insulin secretion (24) .…”
Section: Discussionmentioning
confidence: 99%